The Jewish Contribution to Lithuanian Independence 1918/1919 - Ruth Leiserowitz (Acta Historica Universitatis Klaipedensis, 2019)
Historians have already shown how the Jewish minority contributed to the rebirth of the Lithuanian state in 1918. The beginning of the experiment to integrate the Jewish minority into the reemergent Lithuanian state, however, has often been told from the perspective of failure only. The article challenges this view, by describing how Zionism, the Jewish national movement, supported the emergence of the Lithuanian state. The author analyses how the Jews supported the newly created Lithuanian government by voting to send representatives to it, and by producing a document that improved the international position of the Lithuanian delegation at the Paris Peace Conference, and which was helpful for the international recognition of the young state.